Anti‐attractant activity of (+)‐trans‐4‐thujanol for Eurasian spruce bark beetle Ips typographus: Novel potency for females. Issue 5 (14th February 2022) - Jirošová, Anna; Kalinová, Blanka; Modlinger, Roman; Jakuš, Rastislav; Unelius, C. Rikard; Blaženec, Miroslav; Schlyter, Fredrik
Abstract: BACKGROUND: Eurasian spruce bark beetles ( Ips typographus ) use both attractant and anti‐attractant semiochemicals to find suitable mature host trees. Trans ‐4‐thujanol is abundant in young, unsuitable spruce trees. Electrophysiological studies have demonstrated its high activity levels, but field data are lacking. RESULTS: Enantioselective GC–MS analysis showed that only (1 R, 4 S )‐(+)‐ trans‐ 4‐thujanol was present in Norway spruce bark volatiles. In a factorial design field‐trapping experiment, trans ‐4‐thujanol alone was not attractive to Ips typographus . Traps baited with I. typographus' aggregation pheromone and trans ‐4‐thujanol or the known anti‐attractant 1, 8‐cineole caught fewer beetles than those baited with the aggregation pheromone alone. Catches for trans ‐4‐thujanol and 1, 8‐cineole were dose‐dependent. Intermediate doses of trans ‐4‐thujanol and 1, 8‐cineole had a similar effect. Surprisingly, in contrast to 1, 8‐cineole and other known Ips anti‐attractants, which all inhibit males more strongly than females, the addition of trans ‐4‐thujanol to the aggregation pheromone reduced the attraction of females more. CONCLUSION: The Norway spruce volatile (+)‐ trans ‐4‐thujanol is a novel I. typographus anti‐attractant with potency comparable to the known anti‐attractants 1, 8‐cineole and verbenone, and is more effective for females than for males. Incorporating (+)‐ trans ‐4‐thujanol into anti‐attractant lures could improve protection of trees from mass attack by I. typographus . Abstract : Enantiomer of Norway spruce compound (+)‐(1 R, 4 S, 5 S )‐ trans ‐4‐thujanol showed in trap experiment anti‐attractant power for Ips typographus with efficiency for females. (+)‐ Trans ‐4‐thujanol is a candidate for semiochemical‐based management for this spruce‐killing pest insect. © 2022 Society of Chemical Industry.